2011
DOI: 10.1016/j.jcin.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Evaluation of a Novel Robotic-Assisted Coronary Angioplasty System

Abstract: Early clinical experience with a robotic-assisted angioplasty system demonstrated feasibility, safety, and procedural effectiveness comparable to manual operation. In addition, the total operator exposure to radiation was significantly low. A larger study is warranted to verify the safety and effectiveness of robotic-assisted percutaneous coronary intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(71 citation statements)
references
References 12 publications
0
70
0
Order By: Relevance
“…This primary end point was achieved in all patients and no device failures occurred. 1 The findings of the multicentre PRECISE study 2 were reported in 2013. In this study, the safety and effectiveness of robotically assisted PCI was evaluated in 164 patients with coronary artery disease.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This primary end point was achieved in all patients and no device failures occurred. 1 The findings of the multicentre PRECISE study 2 were reported in 2013. In this study, the safety and effectiveness of robotically assisted PCI was evaluated in 164 patients with coronary artery disease.…”
Section: Resultsmentioning
confidence: 98%
“…1 These individuals had single coronary artery stenoses with a mean lesion length of 11 mm in target vessels 2.5-4.0 mm in diameter. The mean procedure time was 43 min with a mean fluoroscopy time of 11.5 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catheter is maneuvered by both the joystick and the touch screen. The remote navigation system has underwent a series of modifications and now is called CorPath 200 System which is produced by Corindus [9] [10]. Despite the device's appearance changs a lot, the basic concept of CorPath 200 is similar to RNS.…”
Section: Introductionmentioning
confidence: 99%
“…Following a series of successful animal studies, a firstin-man registry was reported in which eight patients with obstructive coronary artery disease underwent roboticassisted percutaneous coronary intervention [12]. All lesions treated were type A or B1.…”
mentioning
confidence: 99%